THE DETERMINATION OF CREDIT RATING OF A LEGAL ENTITY WITH REGARD TO THE PROBABILITY OF BANKRUPTCY - Natalia Alekseevna Lazareva (Современная наука и инновации)
The risk of non-repayment of a credit issued by a bank to a legal entity, as well as the need to avoid the bankruptcy of the enterprise require participants to credit transactions continuously monitoring the financial condition of the borrower and the assessment of its solvency rating. This allows making an informed decisioning for a loan, as well as the desirability of the continuation of the credit relationship with the borrower